Efektivitas Pemanfaatan Youtube sebagai Media Sharing Video Pembelajaran Praktik Video Editing bagi Mahasiswa : (Studi Kasus Perkuliahan Editing video di Sekolah Tinggi Multi Media (STMM) Yogyakarta) - Dina Dwika Oktora (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This research evaluates the effectiveness of the YouTube platform as a video sharing medium for learning video editing practices at Sekolah Tinggi Multi Media Yogyakarta (STMM). Video sharing platforms such as YouTube have a significant role in supporting independent learning, enabling flexible access to material, and giving students opportunities to develop editing skills. This research data was obtained from questionnaires and in-depth interviews with students enrolled in the Video Editing course at STMM Yogyakarta. The research results show that YouTube plays an effective role as a supporter of independent learning and a complement to face-to-face learning, but does not completely replace direct interaction with lecturers. Using YouTube also faces several obstacles, such as limited internet connection, limited appropriate content, and dependence on visualization without in-depth theoretical understanding. This research recommends optimizing video curation, integrating discussion platforms, and regular monitoring and evaluation.